2016
DOI: 10.1155/2016/1813403
|View full text |Cite
|
Sign up to set email alerts
|

High Precision Clock Bias Prediction Model in Clock Synchronization System

Abstract: Time synchronization is a fundamental requirement for many services provided by a distributed system. Clock calibration through the time signal is the usual way to realize the synchronization among the clocks used in the distributed system. The interference to time signal transmission or equipment failures may bring about failure to synchronize the time. To solve this problem, a clock bias prediction module is paralleled in the clock calibration system. And for improving the precision of clock bias prediction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The delay of Atomic clock [3] The delay of Photoelectric modulation [4] The delay of Optical fiber dispersion [5] The delay of The troposphere [6] The delay of Ionospheric layer [7] The delay of Sagnac effect [8] The delay of Theory of relativity [9] The delay of temperature [10] 10E-11s In the existing satellite-earth time comparison model of special relativity, researchers discuss all the delay in the process of satellite-earth time comparison, which are arranged in downlink order according to the order of delay, as shown in Table 1.…”
Section: Tab1 Current Research Progressmentioning
confidence: 99%
“…The delay of Atomic clock [3] The delay of Photoelectric modulation [4] The delay of Optical fiber dispersion [5] The delay of The troposphere [6] The delay of Ionospheric layer [7] The delay of Sagnac effect [8] The delay of Theory of relativity [9] The delay of temperature [10] 10E-11s In the existing satellite-earth time comparison model of special relativity, researchers discuss all the delay in the process of satellite-earth time comparison, which are arranged in downlink order according to the order of delay, as shown in Table 1.…”
Section: Tab1 Current Research Progressmentioning
confidence: 99%
“…However, dividing confusion area with the same width lacks generality. Meanwhile, time synchronization is the prerequisite of coordinating distributed system operations [26]. During operating the passive system, time synchronization with high precision must be got and kept.…”
Section: Signal Detectionmentioning
confidence: 99%
“…Determining the OWSL has been studied considerably in the past. Michelson-Morley experiment and Kennedy-Thorndike experiment [8] have shown that the TWSL is independent of the closed path considered, and is isotropic. Although the average speed of TWSL can be measured, the OWSL is still undefined.…”
Section: Introductionmentioning
confidence: 97%